2016
DOI: 10.3390/foods5020029
|View full text |Cite
|
Sign up to set email alerts
|

Food Safety Impacts from Post-Harvest Processing Procedures of Molluscan Shellfish

Abstract: Post-harvest Processing (PHP) methods are viable food processing methods employed to reduce human pathogens in molluscan shellfish that would normally be consumed raw, such as raw oysters on the half-shell. Efficacy of human pathogen reduction associated with PHP varies with respect to time, temperature, salinity, pressure, and process exposure. Regulatory requirements and PHP molluscan shellfish quality implications are major considerations for PHP usage. Food safety impacts associated with PHP of molluscan s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 72 publications
0
32
0
1
Order By: Relevance
“…The conventional approach to purification of bivalve fails to reduce vibrios (Croci et al . ; Andrews ) while innovative postharvest treatments are expensive, kill bivalves and do not satisfy those consumers who praise for live bivalves (Mississippi Department of Marine Resources USA ; Baker ). Since it has been widely demonstrated that BALOs cannot grow in eukaryotic cells (Ruby ), they do not represent a specific risk for human safety.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional approach to purification of bivalve fails to reduce vibrios (Croci et al . ; Andrews ) while innovative postharvest treatments are expensive, kill bivalves and do not satisfy those consumers who praise for live bivalves (Mississippi Department of Marine Resources USA ; Baker ). Since it has been widely demonstrated that BALOs cannot grow in eukaryotic cells (Ruby ), they do not represent a specific risk for human safety.…”
Section: Discussionmentioning
confidence: 99%
“…Handling and processing are essential to reduce the risk of V. parahaemolyticus infection because of consuming oysters. The steps involved in handling and processing of oysters are receiving, storing, washing, packaging, and distributing oysters to the customer (Baker, 2016). Incorrect handling and processing can allow initially low concentrations of V. parahaemolyticus to increase and become dangerously high in oysters.…”
Section: Factors Affecting the Accumulation Of V Parahaemolyticus Inmentioning
confidence: 99%
“…Mahmoud and Burrage (2009) reported that 5 kGy of irradiation reduced the concentration of V. parahaemolyticus in whole oysters from 7 log MPN/g to a nondetectable (<1 log CFU/g) concentration. Although irradiation effectively reduced the number of V. parahaemolyticus in oysters, the application of this method may only be allowed in some countries with specific requirements (Baker, 2016). Furthermore, the widespread use of this method has been reported to be limited by the small number of irradiation facilities and low consumer acceptance of irradiated oysters (Baker, 2016; Ravindran & Jaiswal, 2019).…”
Section: Intervention Strategies For Eliminating V Parahaemolyticusmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, George Baker summarizes and discusses current information on post-harvest processing (PHP) methods to help ensure the safety and quality of bivalve molluscan shellfish. [8]. …”
mentioning
confidence: 99%